Atmospheric Water Monitoring by Using Ground-Based GPS during Heavy Rains Produced by TPV and SWV - Guoping Li; Jia Deng (Advances in Meteorology)
The time series of precipitable water (PW) in 30 min intervals has been determined through experimentation and operational application of a ground-based global positioning system (GPS) network in Chengdu Plain, which is used for precise and reliable meteorological research. This study is the first to apply PW to the southwest vortex (SWV) and heavy rain events by using the data from an intensive SWV experiment conducted in summer 2010. The PW derived from the local ground-based GPS network was used in the monitoring and analysis of heavy rain caused by the SWV and the Tibetan Plateau vortex (TPV). Results indicate that an increase in GPS precipitable water (GPS-PW) occurs prior to the development of the TPV and SWV; rainfall occurs mainly during high levels of GPS-PW. The evolution features of GPS-PW in rainfall process caused by different weather systems over the Tibetan Plateau (TP) also differ. These results indicate the reference values for operational applications of GPS-PW data in short-term forecasting and nowcasting of high-impact weather in addition to further investigation of heavy rain caused by the TPV, SWV, and other severe weather systems over the TP.